VET Data Report Germany 2010 : facts and analyses accompanying the Federal report on vocational education and training - Friedrich, Michael [Herausgeber]; Hanf, Georg [Herausgeber]; Strohmaier, Eckart [Herausgeber] (Bundesinstitut für Berufsbildung, 2011)
"The Data Report accompanying the 2010 Report on Vocational Education and Training represents the second issue of this work. The first two chapters present the current situation in initial vocational training and in continuing vocational training as well as highlighting the changes which have taken place over the course of time. The main thematic focus of the 2010 Data Report is the transition from training to employment. The report then provides information on international indicators and finally on mobility as part of VET. This English version gives only a selection of the main findings." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.3.1 Ausbildung im Dualen System; S 1.5.2 Berufliche Weiterbildung; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.3.3.3 Mobilität; Berufsbildungsbericht; Berufsbildungsstatistik; Berufsbildungspolitik; Berufsausbildung; Ausbildungsstellenmarkt; Berufliche Weiterbildung; Berufseinmündung; Zweite Schwelle; Mobilität; Indikatoren